Research on the Impact of the Strength of Channel Conflict on Cross-Channel Integration: The Mediating Effect of Channel Fluency and Stability - Dong, Wei-Wei; Lu, Qing-yan (Frontiers in Psychology, 2022)
Based on event system theory, from the perspective of manufacturers, we explore the effect of the strength of channel conflict on cross-channel integration, and then analyzes the mediating effect of channel fluency and channel stability. Taking manufactures who implement cross-channel integration as research samples, and basing the data collected from 229 respondents, the study uses multiple regression analysis and Bootstrap method to test the research hypotheses. The empirical research findings show that: the strength of channel conflict plays a negative role on channel fluency and channel stability; the strength of channel conflict has a double-edged sword effect on cross-channel integration: it can reduce cross-channel integration by destroying channel fluency, and at the same time can improve cross-channel integration by destroying and reducing channel stability.